Treatment in transient synovitis cases: A review - Sananta, Panji -; Anggadha, Fernaldhi -; Fuzianingsih, Eka Noviya (Universitas Muhammadiyah Surabaya, 2024)
Inflammation of the synovial membrane of a joint is a common symptom of transient synovitis (TS), which is the medical term for a condition that leads to hip discomfort in juvenile patients. The estimated annual incidence of TS is 0.2%, and the risk of developing the disease over one's lifetime is 3%. Unfortunately, the specific pathophysiology of TS is still unclear. Therefore, the particular treatment is still debatable. There are several methods of treating TS, starting with bed rest in the hospital and using analgesics, steroids, skin traction, and joint aspiration. Most of the time, transient synovitis is a self-limiting condition that heals independently and is managed conservatively by monitoring and rest. Several medical therapy options, including analgesics, NSAIDs, and corticosteroids, speed up healing. On the other hand, skin traction is also reported to provide beneficial therapeutic effects for TS patients. Thus, with many therapeutic options, TS's